The Influence of Fourth Party Logistics Services on Performance of Manufactuirng Sector in Kenya: A Study in Food and Beverage Manufacturing Firms - Naomy Jepchumba (Britain International for Academic Research (BIAR) Publisher, 2023)
The aim of this study was to establish the relationship between fourth party logistics services and performance of food and beverage manufacturing companies in Kenya. This research study adopted a descriptive and cross-sectional research designs. Data was collected from the food and beverage manufacturing firms using self-administered questionnaires. The data collected was analyzed by use of descriptive and inferential statistics. The findings from the study revealed that freight management, logistics information systems management, customer relations management and product Packaging had a significant influence on the performance of food and beverage processing firms. The study concluded that fourth party logistics through freight management, logistics information system, customer relations management and product Packaging were critical in enhancing the performance of food and beverage processing firms in Kenya. The study recommends that the management of food and beverage processing firms ought to embrace fourth party logistics services by having a freight management framework, enhancing use of logistics information systems, bringing customers on board and embracing effective and innovative ways of Packaging the products in order to gain performance.